Hubungan Antara Kecerdasan Emosional dengan Perkembangan Sosial Siswa Kelas XI IA MAN 2 Model Medan Helvetia - Mirza Irawan; Rospita Sitorus (Lembaga Intelektual Muda (LIM) Maluku, 2023)
The purpose of this study was to determine the relationship between emotional intelligence and social development of class XI IA MAN 2 Model Medan Helvatia in the 2022/2023 Academic Year. The method in this study is a quantitative method with a correlational research design. The population in this study were students of class XI IA MAN 2 Model Medan. Sampling in this study used random sampling using the slovin formula. The sample size is 85 students. The data collection tool used is a questionnaire. The validity of the questionnaire was obtained by product moment correlation and the reliability test was obtained by the Cronbach alpha test. Test the hypothesis using the product moment formula from pearson with the help of SPSS22 For Windows. The results of the analysis showed r = 0.628 and Rsquare = 0.386 and a significant value of 0.000 (p <0.05). Based on these results, the research hypothesis was put forward: